2008
DOI: 10.1159/000114173
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Behaviors of Female Teachers Related to Breast Cancer and Breast Examination in Southern Turkey

Abstract: Background: The aim of this study was to investigate the knowledge, attitudes, and behaviors of female teachers related to breast cancer in Southern Turkey. Materials and Methods: There are almost 5,000 female teachers working in Hatay, Turkey, and we aimed to reach 10% of this population. Our questionnaire consisted of 14 questions about personal information, 14 questions about knowledge related to breast cancer, and 14 questions about attitudes and behaviors of teachers. Results: In all, 490 female teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The present study showed that women demonstrated higher knowledge of breast cancer screening and risk factors and were more likely to perform BSE compared to other recent studies in neighbouring countries [24][25][26]. Similar to previous studies [23,25,27] the most familiar methods was BSE followed by CBE and mammography.…”
Section: Discussionsupporting
confidence: 86%
“…The present study showed that women demonstrated higher knowledge of breast cancer screening and risk factors and were more likely to perform BSE compared to other recent studies in neighbouring countries [24][25][26]. Similar to previous studies [23,25,27] the most familiar methods was BSE followed by CBE and mammography.…”
Section: Discussionsupporting
confidence: 86%
“…Media, internet, hospitals, primary health care clinics, and friends and acquaintances play roles in educating the public and increasing awareness about the importance of BSE (Thomas et al, 2002;Dündar et al, 2006;Temiz et al, 2008). In the present study, internet, television, and hospital or primary health care clinic were the most common sources of information concerning BSE for both groups.…”
Section: Discussionmentioning
confidence: 54%
“…Studies show that the printed and television media are the main source of information for women 12,19,20,27,32,33 . In national studies, Brito et al 12 demonstrated that the media was the second source of information about mammography (17.1%), and Santos et al 27 showed they were the third main source of information (10.9%).…”
Section: Rev Bras Epidemiol 2013; 16(4): 930-42mentioning
confidence: 99%
“…In national studies, Brito et al 12 demonstrated that the media was the second source of information about mammography (17.1%), and Santos et al 27 showed they were the third main source of information (10.9%). However, in international studies 19,20,32,33 , more than 50% of the women mention the means of communication 2013; 16(4): 930-42 as the main source of information. The way the media transmits the information about the early diagnosis can be incomprehensible; even though the central theme is clear, the questions related to it are not 25 .…”
Section: Rev Bras Epidemiol 2013; 16(4): 930-42mentioning
confidence: 99%
See 1 more Smart Citation